Pendekatan Metakognitif untuk Meningkatkan Kemampuan Penguasaan Konsep dan Pemecahan Masalah Matematika Siswa Kelas XII Jurusan IPA MAN 2 Pesisir Selatan - Artita Salmi (Departement of Mathematics Education, 2023)
This study aims to find out how students' ability to master mathematical concepts and solve mathematical problems after implementing learning with a metacognitive approach. This type of research uses an experimental method. The design used in this study was a pretest–posttest control group design. The population in this study were all students of class XII IPA which were divided into 2 classes, both of which were directly sampled. The results of the study showed that first, students' ability to master concepts and solve mathematical problems as a whole, before being given learning with a metacognitive approach and conventionally did not differ, both were almost the same, namely 63.12 and 61.72. Prior to learning, the ability to master the concept and solve mathematical problems of students who will be taught with a metacognitive approach is slightly better than students who will be given conventional learning. Second, students who received learning with a metacognitive approach obtained an increase in their ability to master concepts and solve mathematical problems better than students who studied mathematics with conventional learning methods, namely experiencing an increase of 0.84 with conventional learning methods and 7.58 in learning with a metacognitive approach. Third, the learning gain of students whose learning is done using a metacognitive approach is overall better than the learning gain of students whose learning is conventional, even though both are in the moderate category. Student learning gains in the aspect of understanding concepts are not too different between students who learn with a metacognitive approach and students who learn conventionally.